2021
DOI: 10.1007/s00590-021-03070-5
|View full text |Cite
|
Sign up to set email alerts
|

Trapeziectomy versus joint replacement for first carpometacarpal (CMC 1) joint osteoarthritis: a systematic review and meta-analysis

Abstract: Purpose This systematic review and meta-analysis directly compares joint replacement (JR) and trapeziectomy techniques to provide an update as to which surgical intervention is superior for first carpometacarpal (CMC-1) joint osteoarthritis. Methods In August 2020, MEDLINE, Embase and Web of Science were searched for eligible studies that compared these two techniques for the treatment of CMC-1 joint osteoarthritis (PROSPERO registration ID: CRD42020189728… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“… 29 Implant arthroplasty is prone to early failure. 4 All of the listed methods include substantial downtime with a delayed return to work and orthosis fabrication of around 6 weeks. Carpometacarpal joint denervation, in comparison, has minimal downtime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Implant arthroplasty is prone to early failure. 4 All of the listed methods include substantial downtime with a delayed return to work and orthosis fabrication of around 6 weeks. Carpometacarpal joint denervation, in comparison, has minimal downtime.…”
Section: Discussionmentioning
confidence: 99%
“… 1 There are a spectrum of surgical options for patients with CMC arthritis, including CMC arthroscopy with debridement, trapeziectomy with or without ligament reconstruction and tendon interposition, trapeziectomy with implant suspensionplasty, arthrodesis, and implant arthroplasty. 3 , 4 , 5 While these procedures are associated with improvements in pain and functional outcomes, there is a substantial risk of postoperative complications, such as tendon rupture; loosening, extrusion, or failure of protheses; and worsening carpal instability. A review of the literature shows that rates of adverse outcomes or postoperative complications can be as high as 22%.…”
mentioning
confidence: 99%
“…Higher medium-term key pinch strength seems to be a great advantage of a TMJ implant arthroplasty (Lee et al, 2021;Raj et al, 2022). The higher strength achieved after Touch V R implant arthroplasty can be explained by the ability of this device to restore biomechanical function.…”
Section: Discussionmentioning
confidence: 99%
“…71 All surgical techniques have demonstrated efficacy in pain relief and functional improvement. [72][73][74] A 2015 Cochrane review by Wajon et al 73 reported that of 7 surgical techniques, none was associated with better outcomes than alternative techniques for outcomes of functioning and pain.…”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…In the US, the most commonly performed technique is trapeziectomy with ligament reconstruction and tendon interposition (>90%), followed by trapeziectomy alone, joint replacement, and fusion, all performed at a similar frequency . All surgical techniques have demonstrated efficacy in pain relief and functional improvement . A 2015 Cochrane review by Wajon et al reported that of 7 surgical techniques, none was associated with better outcomes than alternative techniques for outcomes of functioning and pain.…”
Section: Thumb Cmc Joint Arthritismentioning
confidence: 99%